2018
DOI: 10.15666/aeer/1601_819836
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF PHOSPHORUS ON N, P, K, Mg ACCUMULATION AND PLANT GROWTH OF DIFFERENT CITRUS ROOTSTOCKS

Abstract: Abstract. Phosphorus is an essential nutrient for the growth of citrus plants. A pot experiment was conducted in greenhouse to investigate the citrus cultivars grafted on 10 rootstocks (Cuningmeng, Suanju, Suancheng, Honglimeng, Zhike, Goutoucheng, Xiangyuan, Hongju, Xiangcheng, and Zhicheng) in response to the different phosphorus treatments viz, low P (LP) = 0.01 mmol L −1 , moderate P (MP) = 0.5 mmol L −1 , high P (HP) = 1 mmol L −1 ) concentrations. All P concentrations were employed in pots containing Hoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…On the other hand, the lack of P in the nutrient solution reduces the concentration of Ca and Mg in the shoots of the BA seedlings. Moreover, P deficiency in the soil is one of the critical aspects that limits the production and yield of many plants; high or low concentrations of P may stop the absorption of elements such as N, K, Fe, Zn and B (Tu et al, 2018). In agreement with these results, Tu et al (2018) showed that low P application in citrus rootstocks can reduce the concentration of Mg in the leaves and thus reduce the photosynthetic activity of the leaves, ultimately reducing the dry weight of the plant.…”
Section: Concentration Of Nutrients In the Shootmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the lack of P in the nutrient solution reduces the concentration of Ca and Mg in the shoots of the BA seedlings. Moreover, P deficiency in the soil is one of the critical aspects that limits the production and yield of many plants; high or low concentrations of P may stop the absorption of elements such as N, K, Fe, Zn and B (Tu et al, 2018). In agreement with these results, Tu et al (2018) showed that low P application in citrus rootstocks can reduce the concentration of Mg in the leaves and thus reduce the photosynthetic activity of the leaves, ultimately reducing the dry weight of the plant.…”
Section: Concentration Of Nutrients In the Shootmentioning
confidence: 99%
“…In addition, leaf chlorosis due to K deficiency can be due to oxidative degradation of chloroplasts and chlorophyll molecules due to increased production of oxygen free radicals (ROS) (Cakmak, 2005). Leaf chlorosis in the absence of N and P can be directly related to the lack of these elements in the structure of the chlorophyll molecule or indirectly due to the reduced absorption of other elements such as Fe, Mn and Mg (Taiz and Zeiger, 2010;Chen et al, 2018;Tu et al, 2018). In confirmation of this, Figure 1E shows that the concentration of shoot Mg in the BA seedlings was 44% and 52% lower in N and P deficiencies, respectively, than in the control plants.…”
Section: Chlorophyll and Spadmentioning
confidence: 99%